Sejarah dan Perkembangan Dakwah di Jepun - M. Samarrai, Salih; Hj. Ali @ Mat Zin, Aizan (Jurnal Usuluddin, 2000)
This paper deals with issues concerning development of da'wa Islamiyyah in Japan. It discusses the da'wa media, individual and groups contributions in propagating Islam and building Muslim communities in Japan. Further, it reveals da'wa activities carried by Japanese and non-Japanese Muslims.